What Drives Investors Toward Dividend-Paying Stocks? An Analysis of Investment Intention (Quest Journal of Management and Social Sciences, 2026)
Background: Dividend-paying stocks attract investors by offering regular income and potential capital growth. Investment intentions are influenced by financial attitudes, financial behavior, and social influences, as explained by the Theory of Planned Behavior. However, challenges such as difficulty tracking dividends, higher taxes, and unequal distribution affect investor decisions and highlight the need for improved dividend management systems.Purpose: The main purpose of this study is to investigate the factors influencing investor’s investment decision for dividend in the stock market.Design/methodology/approach: Explanatory research design is employed in this study. This study is based on theory of planned behavior/ theory of reasoned action. It used a convenience sampling technique, and a total of 403 respondents are interviewed using a structured questionnaire, where data is collected by using the KOBO toolbox. Both descriptive and inferential statistics are used to examine the data quantitatively. SEMFindings: Findings show that majority of investors prefer stock dividends over cash dividends. Subjective norms, financial attitude, and financial behavior have significant impact on individual's intention to invest.  Major challenges faced by the investor Quest International College, Pokhara University, Gwarko, Lalitpur, Nepal were identified to be difficulty in tracking dividend payments, higher tax, and Unequal distribution. Streamlining dividend tracking processes, implementing tax reforms to reduce the tax burden on dividends, and promoting equitable dividend distribution can enhance investment experience for investors and foster a more favorable investment environment.Conclusion: Investors preferred stock dividends over cash dividends where Saving Amount and Self-Income are major sources for Investment. Subjective norms, financial attitude, and financial behavior all can play a role in shaping an individual's intention to invest in stocks for dividend purposes. Difficulty in tracking dividend payments, higher tax, and Unequal distribution are the major issues for investors which can be minimized by streamlining dividend tracking processes, implementing tax reforms to reduce the tax burden on dividends, and promoting equitable dividend distribution.Keywords: Investment Decision Making, Dividend, Secondary Share Market, Investors Behaviors